Enhanced BTX Production in Refineries with Sulfur Dioxide Oxidation by Thermal Integrated Model. Issue 9 (26th July 2018) - Karimi, Mohsen; Rahimpour, Mohammad Reza; Iranshahi, Davood
Abstract: More stringent environmental regulations as well as limitations of traditional energy sources lead to the development of innovative techniques to supply the required energy of different industries. Multifunctional autothermal reactors as a novel strategy in process integration technology have been introduced as a response to this requirement. The catalytic naphtha reforming process is one of the main processes in the refinery industries which demand several sources of energy to manage the existing reactions. Also, oxidization of sulfur dioxide to sulfur trioxide as a highly exothermic reaction is one of the typical solutions to reduce and control this greenhouse gas in various industries. According to the main aims of process integration and by considering environmental regulations, a novel thermal integration model is proposed. The results demonstrate the aromatic upgrading and high conversion of sulfur dioxide in this model. Abstract : Multifunctional autothermal reactors as a novel strategy in process integration technology have been introduced to supply innovative energy to industries. A novel thermal integrated model with the combination of SO2 oxidization and catalytic reforming process iss proposed. Reduction of energy consumption in the oil refineries is achieved and the production rate in naphtha reforming is improved.